What is the best management of ovarian failure in women with Turner syndrome?. Issue 7 (July 2017) - Tichenor, Vincent; Snyder, Matthew
Abstract : EVIDENCE‐BASED ANSWER : Parenteral estrogen starting at age 12 is associated with about 6 cm more growth than oral estrogen (SOR: B, cohort study). It is unclear if starting parenteral estrogen at age 12 or 14 makes a difference (SOR: B, underpowered RCT). Transdermal estrogen therapy is associated with achieving at least Tanner stage 4 and more growth than expected by historical standards. All patients with Turner syndrome should receive estrogen at age 12 and cyclic progesterone 2 years later to induce sexual maturity (SOR: C, expert opinion).